Pelatihan Pembelajaran Materi Seni Rupa Modern Dengan Menggunakan Video BBC Master of Modern Arts Dalam Bahasa Inggris di Parangtambung Makassar - Erlangga Makawi , Faizal; Arnidah, Arnidah; Pattaufi, Pattaufi; Sri Rika Amriani. H; Aswan, Dedy (Jurusan Matematika FMIPA UNM, 2023)
The purpose of this learning activities is to enhance the knowledge of arts practitioners who lived in Parangtambung region of Makassar. The training materials utlisize BBC videos of Master of Modern Arts topic, which aim to provide relevant understanding of the development of art in Makassar. The training materials are in English to provide insight and motivatio for participants to have an awarness of the importance English as International Language. The BBC Maste of Modern Arts video explains the historical development of modern art, from the process, method to the end result. The results of this activity show an improvement in participants’ knowledge of visual arts and understandin English videos. The outcomes achieved in this training activity are ; (1) the participants’ knowledge of modern arts in today’s world becomes relefant; (2) participants’ English Language competency in terms of memorizing vocabularies and listening comprehension is improved..